2021
DOI: 10.1136/rapm-2020-102040
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral block for the prevention of chronic postsurgical pain after breast cancer surgery

Abstract: Patients frequently report chronic postsurgical pain (CPSP) after breast cancer surgery (BCS). The paravertebral block (PVB) is an effective technique to reduce acute postoperative pain after BCS, but its efficacy in preventing CPSP is unclear. This meta-analysis evaluates the efficacy of PVB in preventing CPSP after BCS. We searched Medline, Embase, CENTRAL, Database of Abstracts of Reviews of Effects, ClinicalTrials.gov, and WHO International Clinical Trials Registry Platform for studies comparing PVB with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…As previously mentioned, CPSP intensity is often related to the presence of a neuropathic component [3,21]. A systematic review (seven RCTs, N ¼ 2087) found lowquality evidence for a protective effect of PVB against chronic neuropathic pain at 12 months after breast cancer surgery (OR 0.51; 95% CI 0.31-085) [22]. This systematic review included both the RCT of Abdallah et al [23] and the large RCT (N ¼ 2108) of Sessler et al [24].…”
Section: Key Pointsmentioning
confidence: 99%
“…As previously mentioned, CPSP intensity is often related to the presence of a neuropathic component [3,21]. A systematic review (seven RCTs, N ¼ 2087) found lowquality evidence for a protective effect of PVB against chronic neuropathic pain at 12 months after breast cancer surgery (OR 0.51; 95% CI 0.31-085) [22]. This systematic review included both the RCT of Abdallah et al [23] and the large RCT (N ¼ 2108) of Sessler et al [24].…”
Section: Key Pointsmentioning
confidence: 99%
“…Numerous factors have been found to be associated with CPSP after breast cancer surgery in the past decade, including socialdemographic, intraoperative, and postoperative factors (6)(7)(8). Several models to predict CPSP have also been developed, mostly in European breast cancer patients (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The paravertebral block is a technique involving the injection of a local anesthetic adjacent to the intervertebral foramina where the spinal nerves exit the thoracic vertebral canal, resulting in ipsilateral segmental sympathetic nerve blockade (18)(19)(20). Paravertebral block is a simple and effective technique for unilateral procedures, with minimal incidence of hypotension and urinary retention (7,21).…”
Section: Introductionmentioning
confidence: 99%